2019
DOI: 10.1002/ijgo.12753
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of subsequent insulin requirement for glycemic control during pregnancy at diagnosis of gestational diabetes mellitus

Abstract: Objective To determine maternal and biological parameters at diagnosis of gestational diabetes mellitus (GDM) as predictors of antenatal insulin therapy (AIT) for glycemic control. Methods In this planned secondary analysis of a prospective observational study, we recruited women diagnosed with GDM between July 1, 2014, and October 31, 2015. Maternal and biological parameters were analyzed as predictors of AIT using multivariable logistic regression analyses. Predictive accuracy of a cut‐off value for a biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
2
29
1
2
Order By: Relevance
“…The insulin requirement among our GDM women (8.7%) was low in comparison to other published data (10.8–52.8%) [ 5 , 20 , 21 , 22 , 26 , 27 , 28 ]. Singapore, which has a similar multi-ethnic population to Malaysia, reported a comparable rate to ours (5.6–10.4%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The insulin requirement among our GDM women (8.7%) was low in comparison to other published data (10.8–52.8%) [ 5 , 20 , 21 , 22 , 26 , 27 , 28 ]. Singapore, which has a similar multi-ethnic population to Malaysia, reported a comparable rate to ours (5.6–10.4%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 85%
“…Ares et al found that the two-hour plasma glucose level was significantly higher in the insulin-treated group [ 20 ]. The study, alongside several others, discovered that the post-glucose load abnormalities were significant predictors of insulin requirement among GDM women [ 20 , 21 , 23 , 26 , 27 ]. We found that two-hour glucose derangement was significantly associated with diet therapy and reduced the risk of insulin usage.…”
Section: Discussionmentioning
confidence: 95%
“…We obtained similar results with our prediction model, integrating all the maternal and metabolic significant variables associated to the need of insulin. Nonetheless, Ducarme failed to combine maternal characteristics and biological parameters to develop an accurate model ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, early diagnosis of GDM (<24 weeks of gestation), older maternal age, pre-pregnancy BMI>30, previous GDM, family history of diabetes are reported as associated factors to insulin treatment ( 9 12 ). Biochemical parameters indicating poor metabolic glycemic control at the diagnosis of GDM can also predict the need of insulin therapy: HbA1c at diagnosis >5.5% and elevated 1-h and 2-h plasma glucose level at OGTT has been reported to be predictors of pharmacological treatment ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…79,80 Others consider that HbA1c is a reference for insulin therapy but the cut-offs are different. [81][82][83][84][85][86] Tang et al consider that patients with HbA1C≥5.3 require treatment with insulin. 81 González-Quintero et al consider that patients with HbA1C≥6 require treatment with insulin.…”
Section: Application Of Glycosylated Hemoglobin and Glycated Albumin mentioning
confidence: 99%